2020
DOI: 10.3390/ani10050842
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Selenium Source in Preventing Oxidative Stress in Bovine Mammary Epithelial Cells

Abstract: Oxidative stress can cause cell damage. Hydroxy-selenomethionine (HMSeBA) is an organic Se source with emerging antioxidant advantages. The objective of this study was to compare the effects of HMSeBA, selenomethionine (SeMet) and sodium selenite (SS) on the antioxidant response and the ability to resist oxidative stress in bovine mammary epithelial cells (BMEC). The BMEC were treated with 0 (Control), 20, 50, 100 and 150 nM HMSeBA, 100 nM SeMet and100 nM SS for 48 h. The results showed that HMSeBA and SeMet t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In contrast, Cozzi et al reported that organic Se has better meat quality than inorganic Se ( 31 ). Recently, Sun et al reported that SM and hydroxy-selenomethionine (HMSeBA) increased the activity and mRNA abundance of GSH-Px and decreased the activities of SOD and ROS in bovine mammary epithelial cells compared with SS ( 40 ). Gong et al suggested that dietary organic Se supplementation was more efficient in increasing GSH-PX activity and total antioxidant capacity, as well as decreasing the MDA content compared to inorganic Se supplementation ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Cozzi et al reported that organic Se has better meat quality than inorganic Se ( 31 ). Recently, Sun et al reported that SM and hydroxy-selenomethionine (HMSeBA) increased the activity and mRNA abundance of GSH-Px and decreased the activities of SOD and ROS in bovine mammary epithelial cells compared with SS ( 40 ). Gong et al suggested that dietary organic Se supplementation was more efficient in increasing GSH-PX activity and total antioxidant capacity, as well as decreasing the MDA content compared to inorganic Se supplementation ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…When endogenous or exogenous ROS and stimulation factors, such as LPS, stimulate bMECs, the oxidative stress and inflammatory response generated by bMECs reduce vitality and affect the health of the mammary gland, resulting in lactation dysfunction, which is the main cause of cow mastitis (27)(28)(29)(30). The occurrence of mastitis leads to extensive changes in transcriptome profiles, including miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that organic Se sources confer a better protective effect than inorganic sources against different oxidative stress conditions [ 32 , 38 , 39 , 40 , 41 ]. Therefore, upregulation of GPX1 and SELENOP gene expression by OH-SeMet and a further decrease in ROS production induced by H 2 O 2 could maintain effective antioxidant defenses and would help the cell to adapt to and overcome the stress with minimal negative consequences.…”
Section: Discussionmentioning
confidence: 99%